The effects of elicitors on lutein and zeaxanthin accumulation in in vitro cultures of Ruta angustifolia (L.) Pers. - Mohd Hassan, Norazian; Othman, Rashidi; Sulaiman, Shaida Fariza; Mohd Zaifuddin, Fatimah Azzahra (2015)
In this study, the effects of selected elicitors, namely salicylic acid (SA) and methyl jasmonate (MeJa) on lutein and/or zeaxanthin accumulation in callus and shoot cultures of Ruta angustifolia (L.) Pers. were investigated. The carotenoid profile of intact leaves and in vitro cultures of R. angustifolia was initially investigated. The microshoot cultures were elicited with SA at concentrations of 0, 50 and 100 mg/ml whereas MeJa elicitation was studied at concentrations of 0, 20, 40 and 60 mg/mL. The cultures were incubated under 16 hours photoperiod at 25°C and were harvested periodically in 30 days interval for 90 days. Each sample was lyophyllized, extracted and analysed by reversed phase high-performance liquid chromatography (HPLC). The HPLC analysis showed that shoot cultures contained the highest total carotenoids content (14.70 ± 0.84 µg/mg) while lutein and β-carotene were the characteristics carotenoids that present in all R. angustifolia samples. SA elicitation increased accumulation of neoxanthin (15.88 ± 2.16 µg/mg DW), the specific carotenoid of the shoot cultures but decreased other carotenoids as compared to non-elicited cultures. MeJa was found to influence the culture growth and lutein production. The optimal elicitation strategy was MeJa elicitation on microshoot cultures with seven days exposure at 20 mg/mL and subsequent culture of 90 days, which resulted in the highest biomass and lutein production (141.07 ± 19.41 µg/mg DW), two times of non-elicited cultures. The carotenoids content in callus cultures was very low and both SA and MeJa elicitation gave no significant effect on carotenoids accumulation. No zeaxanthin was detected in all samples studied. In conclusion, the enhancement of lutein content in R. angustifolia can be achieved through MeJa elicitation on microshoot culture.